MODEL PEMBACAAN KRITIS TEKS-TEKS KEISLAMAN KAUM FEMINIS - Muhandis Azzuhri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
Study feminism can not be separated from theological studies. Almost all religions have bad treatments against women. The position of women in some religions are placed as